2020
DOI: 10.1007/s00270-020-02622-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Imaging and Procedural Risk Factors for Intrauterine Infective Complications After Uterine Fibroid Embolisation: A Retrospective Case Control Study

Abstract: Introduction This was a retrospective case–control study at a single tertiary centre investigating all UFE procedures between January 2013 and December 2018 for symptomatic fibroids. The aim was to determine the clinical, imaging and procedural risk factors which impact upon the risk of post-uterine fibroid embolisation (UFE) intrauterine infection. Cases were patients which developed intrauterine infection post-procedure, and controls were the background UFE population without infection. Methods Clinical de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Based on the previous researches, we hypothesized that Isorhy could promote autophagy in OA cells via the PI3K/AKT/mTOR pathway. To confirm this hypothesis, we divided the cells into four groups, in order of normal chondrocytes (control), OA chondrocytes [ 1 ], OA cells + 50 μM Isorhy (OA + Isorhy) and OA cells + 50 μM Isorhy + MHY1485 (mTOR activator) (OA + Isorhy + MHY1485), respectively. For the above four groups of cells, RT-PCR analysis was performed, and the results showed (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the previous researches, we hypothesized that Isorhy could promote autophagy in OA cells via the PI3K/AKT/mTOR pathway. To confirm this hypothesis, we divided the cells into four groups, in order of normal chondrocytes (control), OA chondrocytes [ 1 ], OA cells + 50 μM Isorhy (OA + Isorhy) and OA cells + 50 μM Isorhy + MHY1485 (mTOR activator) (OA + Isorhy + MHY1485), respectively. For the above four groups of cells, RT-PCR analysis was performed, and the results showed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Osteoarthritis [ 1 ] is a familiar chronic joint disease that manifests itself as degenerative changes in articular cartilage (changes similar to aging of machine parts) and secondary osteophytes [ 2 4 ]. According to statistics, OA has become one of the most common chronic diseases in the world, affecting about ten percent of men and eighteen percent of women more than the age of 60, and recent studies have shown a trend toward younger onset of OA [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the two most recent studies on fibroid size suggest an increased risk of complications in women with greater fibroid burden. A large retrospective case control study reviewed 333 patients with respect to intra-uterine infection post UAE and identified large uterine volume > 1000 cm 3 to be a risk factor for infective complications although the statistically significance was relatively low ( p = 0.049, OR 2.94 [1.15–7.54] (Mollier et al 2020 ). A systematic review and meta-analysis of four retrospective cohort studies (Katsumori et al 2003 ; Prollius et al 2004 ; Choi et al 2013 ; Bérczi et al 2015 ) was carried out incorporating total of 839 total patients.…”
Section: Uae and Large Fibroidsmentioning
confidence: 99%
“…Similarly, a study of 61 patients showed that larger uterine volume (> 780 cm 3 ) is not associated with reduced symptomatic improvement or higher rate Table 3 Studies of UAE for adenomyosis where the primary outcome was assessed using a validated QOL questionnaire (Froeling et al 2012;Smeets et al 2012;Nijenhuis et al 2015;de Bruijn et al 2017a;de Bruijn et al, 2017b;Siskin et al 2001;Millo et al 2010) NR not reported, AUB abnormal uterine bleeding, HRQOL health related quality of life, UFS-QOL Uterine fibroid symptom and quality of life a same patient cohort with outcomes reported at 3 years and 7 years. The De Bruijn article was not included in the systematic review (Parthipun et al, 2010;Katsumori et al, 2003;Prollius et al, 2004;Firouznia et al, 2008;Choi et al, 2013;Bérczi et al, 2015;Mollier et al, 2020) UAE uterine artery embolisation, NR not reported (Prollius et al 2004). Furthermore, a retrospective analysis of 101 patients found no correlation between size of the dominant fibroid and clinical effectiveness or complication rate at 1 year (Firouznia et al 2008).…”
Section: Uae and Large Fibroidsmentioning
confidence: 99%